Enhancing vocational education through continuous professional development: Analysing the non-degree program for indonesian polytechnic lecturers - Citra Amitiurna; Maya Puspitasari; Muhammad Arifin Pelawi; Putu Hangga Nan Prayoga (Jurnal Pendidikan Vokasi, 2025)
Continuous professional development for lecturers, bolstered by government initiatives, is crucial for their ability to meet the changing requirements of the labour market. This research explored the effects and long-term viability of the Non-Degree Program for Polytechnic Lecturers (NDPKD) in Indonesia. The study employed both open- and closed-ended questionnaires to examine the program's impact on improving vocational education. A total of 512 lecturers from both state and private polytechnics took part in the study. The results indicated that the NDPKD program had a beneficial impact on the competencies of lecturers and fostered enhanced collaboration with industry partners. Participants indicated that their skills and knowledge had improved, resulting in more effective teaching practices and increased engagement with the industry. Nonetheless, a number of challenges arose, such as time constraints, variations in initial skill levels, and a lack of adequate institutional support. The constraints of time posed challenges for lecturers in fulfilling program requirements alongside their current responsibilities. Additionally, the diverse levels of competency highlighted the necessity for more customised training approaches. The lack of substantial institutional support significantly diminished the program's overall effectiveness. The study suggests implementing more adaptable scheduling options, creating tailored training programs, and enhancing the support systems within institutions. By focusing on these elements, we can improve the continuity and sustainability of the NDPKD program, thereby maximising its impact on vocational education in Indonesia.